A Comparison of Circle Hook Size on Hooking Success, Deep Hooking Rate, and Postrelease Mortality of Hatchery-Reared Rainbow Trout. (3rd March 2016) - Sell, Matthew T.; Kazyak, David C.; Hilderbrand, Robert H.; Heft, Alan A.; Cooper, Ryan M.
Abstract: We investigated the effects of circle hook size and angling technique on hooking location, capture success, and postrelease mortality in salmonids by using hatchery-reared Rainbow Trout Oncorhynchus mykiss . Fish were caught using a range of inline circle hook sizes (4, 6, 8, and 10) baited and fished both actively and passively. While hook size had no influence on capture rates, active fishing resulted in significantly higher capture rates. Very few mortalities (2%) were observed across angling methods or hook sizes during 72 h of postrelease monitoring. However, significantly more fish were deeply hooked with passive fishing. Contrary to claims by manufacturers and sportfishing entities, mounting evidence indicates that passively fished circle hooks have lower capture rates and might actually increase deep hooking in salmonids. Received May 19, 2015; accepted November 12, 2015